AIR POLLUTION IN ZIMBABWE: AN ENVIRONMENTAL HEALTH CHALLENGE - MAPIRA, JEMITIAS (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Air pollution is a major environmental problem in industrialized countries such as: the USA, China, Japan and most European countries including: France, Germany, Italy and the UK. One of its major causes is modern technology which depends heavily on fossil fuels (coal and oil) and dates back to the Industrial Revolution, which started some two centuries ago. Although the level of industrialization is quite low in developing countries such as Zimbabwe, air pollution is now posing a threat to the nations environmental security. This paper examines the problem of air pollution in Zimbabwe with a view to suggesting possible solutions. While previous researches have given brief and rather superficial accounts on the problem, this paper seeks to provide an in-depth study on the issue for the benefit of researchers, stakeholders and policy makers. The paper examines issues such as: causes, sources, health impacts, and possible solutions within the legislative and policy framework of Zimbabwe.Based on information that was collected in August 2014, the paper shows that air pollution is a major environmental problem and should be addressed seriously at both local and national levels.